Experimental studies on the terminal velocity of air bubbles in water and glycerol aqueous solution - Liu, Liu; Yan, Hongjie; Zhao, Guojian; Zhuang, Jiacai (Experimental thermal and fluid science, 2016)
•Experiments on the terminal rising velocity of air bubbles were carried out.•The behavior of the terminal velocity under various bubble diameters was discussed.•The accuracy of the correlations for predicting terminal velocity was evaluated. Terminal rising velocity of a single bubble in stagnant water and glycerol aqueous solution was studied by the techniques of high-speed photography and digital image analysis. The results can be summarized as follows: In water, bubble terminal velocity increases while aspect ratio decreases almost linearly in the region where d<0.83mm. Then, both terminal velocity and aspect ratio begin to show a widely scattered trend with the bubble diameter in the range 0.83–6mm. Finally, the level of scattering tends to be weak and the terminal velocity increases gradually while the aspect ratio remains relatively stable when d>6mm. In the surface-tension-dominated regime, the aspect ratio of a single bubble varies significantly with the value fluctuating from 0.4 to 0.99. The aspect ratio should be taken into account with the bubble diameter when predicting the terminal velocity. In the inertia-dominated regime, the terminal velocity increases gradually with increasing the bubble diameter while their aspect ratios vary between 0.4 and 0.7. In the glycerin aqueous solution, as a whole, the terminal velocity increases with bubble diameter and the trend of the bubble velocity does not show a scattered behavior. In water, the most accurate model for predicting terminal velocity throughout the investigated range is given by Tomiyama et al. (2002), and then followed by Ishii and Chawla (1979).